High-intensity interval training to improve fitness in children with cerebral palsy - Lauglo, Reidun (BMJ Open Sport Exerc Med, 2016)
AIM: To evaluate effects of high-intensity interval training (HIT) on aerobic exercise capacity, quality of life, and body composition in children with cerebral palsy (CP). METHODS: This was a baseline control trial. Children with CP, Gross Motor Function Classification System (GMFCS) levels I–IV, and age 10–17 years were included. The primary outcome, peak, and submaximum oxygen uptake (VO(2peak), VO(2submax)) were measured at enrolment to the study (T0), after a pretraining period (T1), and after HIT (T2). Secondary outcomes were quality of life assessed with the KINDL questionnaire, and body composition measured using whole body dual-energy X-ray absorptiometry scanning. The exercise was performed on treadmills and consisted of 24 sessions, each with a total of 16 min of exercise at >85% of maximal heart rate. RESULTS: 20 children were included and 6 children dropped out. VO(2peak) increased by 10%, from a median of 37.3 (31.0–40.1) to 41.0 (36.6–48.5) mL/kg/min from T1 to T2 (p<0.01). VO(2submax) did not change; thereby, the percentage oxygen utilisation was reduced. Body composition was unchanged. Parent-reported quality of life improved, whereas quality of life reported by the children did not improve. CONCLUSIONS: Aerobic exercise capacity improved and per cent utilisation of VO(2max) declined after HIT in children with CP. Therefore, HIT can be a time efficient way to improve maximal capacity, and increase energy reserve in this patient group. TRIAL REGISTRATION NUMBER: NCT00965133.